Innovative Self‐Assembly of 15‐Mer Chimeric α‐Peptide–Oligourea Foldamers toward Cl−‐Selective Ion Channels - Chiranjit Dutta; Pannaga Krishnamurthy; Dandan Su; Jianwei Li; Sung Hyun Yoo; Gavin W. Collie; Morgane Pasco; Jingsong Fan; Min Luo; Mihail Barboiu; Gilles Guichard; R. Manjunatha Kini; et al. (Small Science, 2024)
Constructing artificial ion channels is a challenging task. Herein, the de novo design of transmembrane ion channels made up of amphiphilic peptide–oligourea chimeric helices is described. They consist of an oligourea segment (7‐mer) attached to the C‐terminus of a short peptide (8‐mer). Mass spectrometry (MS) and transmission electron microscopy (TEM) analyses show that in an aqueous solution, two of these chimeras (HPU‐E and HPU‐N) independently form defined oligomeric structures. TEM also shows that they form fiber bundles. The third related chimera HPU‐F does not oligomerize (MS) but forms spherical nanostructures (TEM). HPU‐E and HPU‐N exhibit anion transport activity across lipid bilayers via antiport mechanism (HPU‐N > HPU‐E). The anion selectivity of HPU‐N is Cl−>NO3− > Br−>SCN− > I− > AcO−>F−, which can be due to anion binding within the channels rather than size exclusion. Patch‐clamp data support HPU‐N's Cl− selectivity (PCl−/PI− = 3.26). X‐ray crystal structure (1.77 Å) of HPU‐N reveals well‐packed α‐helices, and cryo‐electron microscopy data shows the formation of nanotubes (13.7 Å diameter pores) and transmembrane channels. The study shows that α‐peptide–oligourea‐based de novo design can yield unique bioactive molecules with defined structures and functions.